1999
DOI: 10.1163/22941932-90001553
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Behaviour of Vascular Cambium in Teak (Tectona Grandis) Growing in Moist Deciduous and Dry Deciduous Forests

Abstract: Seasonal behaviour of vascular cambium in Tectona grandis L. f. growing in Moist Deciduous Forests (MDF) and Dry Deciduous Forests (DDF) of Gujarat State in Western India was studied for one annual cycle. In both the forests active cambial cell division and simultaneous differentiation of xylem and phloem started in June when the dormant shoot buds opened. In MDF cambial cell activity reached its peak in August-September and ceased in October; in DDF it ceased in November after reaching a peak in July-August. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
3
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 12 publications
7
40
3
2
Order By: Relevance
“…The radial sequence of cells corresponds to the temporal sequence of appearance in the trees, allowing wood formation to be assessed over different intra-annual time scales depending on the resolution required by the analysis, from a few hours (Ford et al 1978) to one week Rossi et al 2006b), to several weeks (Bäucker et al 1998;Rao & Rajput 1999). A precise description of the period of wood formation allows the days spent in differentiation by each cell to be estimated (Wodzicki 1971;Horacek et al 1999;Rossi et al 2003).…”
Section: Associate Editor: Nigel Chaffeymentioning
confidence: 99%
“…The radial sequence of cells corresponds to the temporal sequence of appearance in the trees, allowing wood formation to be assessed over different intra-annual time scales depending on the resolution required by the analysis, from a few hours (Ford et al 1978) to one week Rossi et al 2006b), to several weeks (Bäucker et al 1998;Rao & Rajput 1999). A precise description of the period of wood formation allows the days spent in differentiation by each cell to be estimated (Wodzicki 1971;Horacek et al 1999;Rossi et al 2003).…”
Section: Associate Editor: Nigel Chaffeymentioning
confidence: 99%
“…Apesar da maior pluviosidade, a temperatura mais elevada leva a uma maior evapotranspiração. Considerando-se que a atividade cambial está relacionada com os fatores climáticos (Rao & Rajput 1999;Salvador et al 1997), pode-se observar que os espécimes estudados em Serra Talhada apresentam uma maior taxa de esclerificação representada pela maior percentagem de fibras no lenho, corroborando Webber (1936) e Baas (1982. Estes autores observaram que os diferentes componentes anatômicos da madeira resultantes da atividade do câmbio vascular podem apresentar diferenças quantitativas em função das adaptações ao ambiente e situação fisiológica do fluxo da água.…”
Section: Comparação Em Relação Ao Ambienteunclassified
“…Teak (Tectona grandis L.f.) is one of the most well known tropical tree species for its high-quality and prized timber (Rao & Rajput 1999, Bhat & Priya 2004). Teak wood is suitable for multiple uses due to its various favorable characteristics and properties, including fine grain, beautiful golden color, and durability with respect to weather, insects and fungi (Kaosa-ard 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Wood formation started after the budding and continued until the end of the rainy season (Nobushi et al 1996), while drought during active growing season caused false ring formation in teak (Priya & Bhat 1998, Palakit et al 2012. Rao & Rajput (1999) found the maximum radial-growth of teak during the monsoon period, while Kokutse et al (2010) reported that annual ring width is strongly depended on mean monthly temperature and is associated with bud break during the rainy season.…”
Section: Introductionmentioning
confidence: 99%